Implementation Of Islamic Elements As A Parameter For Credit Evaluation Process: Exploring Shariah Adviser's Perceptions - Siti Nor Amira Mohamad; Mohamad Yazis Ali Basah; Muhammad Ridhwan Ab. Aziz (Human Resource Management Academic Research Society, 2024)
Indexed by ERA